A comparison of circular object detection using Hough transform and chord intersection - Mohamed Rizon, Mohamed Juhari; Haniza, Yazid; Puteh, Saad (Institute of Eelectrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org